COVID-19 vs. GFC: A firm-level trade margins analysis using Kenyan data - Socrates Kraido Majune; Kemal Türkcan (World Trade Organization (WTO), 2022)
This study describes trade margins (intensive and extensive) and establishes determinants of the mid-point export and import growth during the global financial crisis (GFC) and COVID-19 pandemic by relying on Kenya's monthly customs transaction data (at 6-digit level of Harmonized System) for the period January 2006-June 2020. Exports fell during the two crises, of which the intensive margin was responsible for the drop during GFC while the extensive margin dominated the COVID-19 era. Imports are mainly driven by the extensive margin which grew during GFCbut declined during the pandemic. However, the fall in the intensive and extensive margins was near symmetrical during the pandemic. Estimates from the fixed-effects regression model reveal that the decrease in export and import mid-point growth was larger during the COVID-19 pandemic than GFC and it was determined by several factors: firm-, product- and partner-country characteristics. Overall, addressing both supply- and demand-side shocks can help countries adjust better to future crises.
Keywords: F02; F14; F23; F60; G01; 330; trade margins; mid-point growth; GFC; COVID-19; Kenya